2014
DOI: 10.1177/1359105314529682
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of body image in children with type 1 diabetes: A case-control study

Abstract: This study evaluated the body image perception in children with type 1 diabetes in order to identify symptoms of disordered eating behaviours early. Children with type 1 diabetes and controls showed underestimation and dissatisfaction with body size. The patients, especially girls, were more accurate in their perception of body size than the control group. The study sheds light on some of the underlying factors that may contribute to the development of disordered eating behaviours in adolescence. The causes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
1
13
1
Order By: Relevance
“…Overall, the current findings corroborate the existing research on general and T1D populations supporting the association between body image problems and DEBs ( Colton et al, 1999 ; Striegel-Moore and Debra, 2002 ; Fairburn and Harrison, 2003 ; Striegel-Moore and Bulik, 2007 ; Kichler et al, 2008 ; Troncone et al, 2016 , 2018 ; Amaral and Ferreira, 2017 ; Falcão and Francisco, 2017 ; Girard et al, 2018 ; Verbist and Condon, 2019 ; Araia et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Overall, the current findings corroborate the existing research on general and T1D populations supporting the association between body image problems and DEBs ( Colton et al, 1999 ; Striegel-Moore and Debra, 2002 ; Fairburn and Harrison, 2003 ; Striegel-Moore and Bulik, 2007 ; Kichler et al, 2008 ; Troncone et al, 2016 , 2018 ; Amaral and Ferreira, 2017 ; Falcão and Francisco, 2017 ; Girard et al, 2018 ; Verbist and Condon, 2019 ; Araia et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…Results from previous studies have been inconclusive as to whether adolescents with T1D are more likely to have body image problems compared with other adolescents. Several researchers found that youths with diabetes more frequently reported concerns and dissatisfaction about their bodies ( Colton et al, 1999 ; Neumark-Sztainer et al, 2002 ; Kichler et al, 2008 ; Shaban, 2010 ; Kaminsky and Dewey, 2013 ; Philippi et al, 2013 ; Pinquart, 2013 ; Kaminsky and Dewey, 2014 ; Troncone et al, 2016 , 2018 ). In contrast, and more in line with the findings of this study, other studies have found no significant differences in body image problems between adolescents with T1D and healthy peers ( Striegel-Moore et al, 1992 ; Meltzer et al, 2001 ; Ackard et al, 2008 ; Kaminsky and Dewey, 2013 ; Falcão and Francisco, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations